PREDICTION OF SOIL PORE WATER PRESSURE RESPONSES TO RAINFALL USING RADIAL BASIS KERNEL FUNCTION - Mohd Anuar, Nurulain Husna (IRC, 2016)
Pore Water Pressure (PWP) prediction is important in analyzing the strength and effective stress of the soil. Increase of PWP will cause slope failure in areas susceptible to landslide. Stability is determined by the equalization of shear strength and shear stress analyses. Knowledge in pore water pressure is important in hydrological analysis, such as seepage slope strength analyses, engineered slope design and assessing slope reactions to rainfall. The main aim of this work is to forecast pore water pressure variations in response to rainfall utilizing Radial Basis Kernel Function and to evaluate model performance using statistical measures.